Modification of Hitball Games in Physical Education, Sports, and Health Learning in School - irsyada, Roas (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2018)
A small ball game is one of the materials contained within the scope of elementary school learning. The kind of small ball game such as Kasti, Rounders, Softball and Baseball. How the result applied of small ball game modification on Physical Education learning process 4th grade on elementary school. This research is a development research that aims to produce products in the form of Hitball game using procedural development model. The type of data used is qualitative and quantitative. The game of Hitball, has contributed to an increase in the student’s pulse rate by 50.97%. In addition, the results of the pulse rate of learners after learning can increase by 73.80% of the maximum pulse rate. From the result of the research, it is concluded that the game of Hitball is in accordance with Core Competencies and basic competencies of Physical Education on Elementary Class IV and can increase the intensity of student movement which is indicated by the increase of the average pulse as much as 50,97%.